A convenient reagent for the conversion of aldoximes into nitriles and isonitriles. Issue 46 (5th May 2020) - Zhang, Wei; Lin, Jin-Hong; Zhang, Pengfei; Xiao, Ji-Chang
Abstract : Described herein is the convenient transformation of aldoximes into nitriles or isonitriles by slightly modifying reaction conditions. Abstract : For the dehydroxylation of aldoximes with 4-nitro-1-((trifluoromethyl)sulfonyl)-imidazole (NTSI), slight modifications of reaction conditions resulted in significantly different reaction paths to provide either nitriles or isonitriles. The challenging conversion of aldoximes into isonitriles was achieved under mild conditions.